Why unions reduce wage inequality: a model of union formation and goal setting - Stennek, Johan (Gothenburg, 2012)
"This paper demonstrates how unions can increase the general wage level by redirecting their bargaining power from wages in general to a focus on the lowest wages. This opportunity arises as a result of the interplay between two sources of market power, namely union bargaining power and an efficiency wage premium earned by skilled labor. This result may explain the stylized fact that unions not only increase wages but also reduce wage inequality. It is also demonstrated that low-wage policies may be part of the reason why unions succeed to organize workers of heterogeneous skills."